2011
DOI: 10.1126/science.1204529
|View full text |Cite
|
Sign up to set email alerts
|

Interventions Shown to Aid Executive Function Development in Children 4 to 12 Years Old

Abstract: To be successful takes creativity, flexibility, self-control, and discipline. Central to all those are ‘executive functions,’ including mentally playing with ideas, giving a considered rather than an impulsive response, and staying focused. Diverse activities have been shown to improve children’s executive functions – computerized training, non-computerized games, aerobics, martial arts, yoga, mindfulness, and school curricula. Central to all these is repeated practice and constantly challenging executive func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

74
1,768
6
148

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,316 publications
(1,996 citation statements)
references
References 41 publications
74
1,768
6
148
Order By: Relevance
“…Secondly, the results of this study suggest potential innovative avenue to intervention. Early childhood trainings enhancing self-control may help alleviate long-term achievement problems [38] and research on normal population samples has shown that executive function abilities including self-control can be trained [39]. According to Rose's public health-oriented approach to preventive medicine shifting the population distribution of a risk factor (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the results of this study suggest potential innovative avenue to intervention. Early childhood trainings enhancing self-control may help alleviate long-term achievement problems [38] and research on normal population samples has shown that executive function abilities including self-control can be trained [39]. According to Rose's public health-oriented approach to preventive medicine shifting the population distribution of a risk factor (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The Raisin Game is an easy and effective tool that has good facevalidity assessing inhibitory control in young children, takes only five minutes and can be used in clinical practice for routine follow-up assessments after preterm birth in order to identify children at risk of attention and learning problems. Executive function abilities can be trained [39] -thus our findings provide potential avenues to interventions aimed at increasing preterm children's long-term achievement. Table 2.…”
mentioning
confidence: 88%
“…identified as an important target for early intervention (Diamond and Lee 2011) due to their 56 positive associations with children's academic achievement (Monette et al 2011;St Clair-57 Thompson and Gathercole 2006; Best et al 2011), as well as their ability to predict future 58 health, socio-economic status, and income (Moffitt et al 2011). Therefore, research 59 demonstrating the benefit of aerobic fitness for cognitive development suggests that higher 60 aerobic fitness may prime children and adolescents' chances for life success in a variety of 61 domains.…”
Section: Luna and Sweeney 2004; Miller And Cohen 2001) Cognitive Conmentioning
confidence: 99%
“…For instance, school programs which promote attentional control, patience and forwardlooking behavior (Diamond & Lee, 2011) may be effective ways of producing lasting changes in conscientiousness (Eisenberg et al, 2014). This may in turn reduce later unemployment levels, although there is not yet strong evidence that such programs improve long-run labor market outcomes.…”
mentioning
confidence: 99%